A responsabilidade do estado na tarefa de garantir o direito de convivência familiar de crianças e adolescentes - Bahia, Claudio José Amaral (2007)
In spite of eighteen years have passed since the 1988 Federal Constitution promulgation, still today it is a reality someone turns up with preoccupying situations involving state omissions in the face of the called fundamental human rights, more exactly in what concerns their application to minority social segments. So, the main theme we intend to accomplish with the present work informed about the practical and adequated difficulties pertinent to them, is the necessary of concretion of the fundamental right of familiar and community companionship toward our children and teenagers, which dogma is expressed assured at the constitutional text, more precisely in the caput of its Art. 227. Following the same way, it will also be object of this study the State responsibility toward the situations that is not possible the concretion of the mentioned fundamental right, because of the public means omission in such cases so that the constitutional subjects injured for such act have, at least, at their disposal, mitigation instruments of the harm caused by the unavoidable absence of familiar companionship, which, without any doubt, will give credit to the isonomy fundamental vector, devised in the caput of the Art. 5th of Lex Legum. The state inaction and omission mentioned above come always to redound to illicit effect, such as, take off the child and the teenager expurgated from the familiar and community companionship the possibility of a kind and condign development, opening for them a way in order to ask for an effective juridical constitutional tutelage having in mind the correction or the mitigation of the mentioned and damaging problem. It will detach the processual ways capable to determine the State responsibility by the omission toward the fundamental right to the familiar and community companionship of the children and teenagers on a real plan, with special prominence to the public civil action, the injunction mandate and the condemnatory knowledge action. Such instruments, informed about the existence of other possibilities, are apt to search for indemnity based upon the theory of civil responsibility called of loss of a chance. Inside this context, what is intended with this work, without any illusion of exhausting the theme, was to bring to a discussion that the familiar and community companionship is a fundamental right essencial to the children and teenagers development; and the State cannot draw back the obligation to give to the less fortunates, efficient conditions in order to reduce the problems concerning to the mentioned absence, under penalty of being responsible for the inconstitutional omission of its acts